Ostatnie już ustępstwo Richarda Rorty’ego na rzecz reprezentacjonizmu - Bińczyk, Ewa (Er(r)go. Teoria - Literatura - Kultura, 2005)
Ewa Bińczyk - Richard Rorty's Last Concession in Favour of Representationism The article, drawing from Richard Rorty’s theory, discusses the notion and the discursive contexts of Representationism.